2013
DOI: 10.1670/11-297
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Habitat Type and the Presence of an Invasive Wetland Plant (Phalaris arundinacea) on Capture Rates of Sympatric Rare and Common Gartersnake Species (Thamnophis butleriandThamnophis sirtalis)

Abstract: Abstract.-Standardized efforts to passively sample for upland snakes often result in low detection probabilities, yet this methodology is often used to determine differences in relative abundance. Estimating abundance of upland snakes using a model that incorporated detection probabilities did not generate useful results because detection rates were too low. These results indicate researchers interested in quantifying relative abundances of upland snakes should focus on increasing sampling efforts in an attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…First, context influences how modes of impact generated by an invader translate to behavioural changes. The characteristics of different animal species can result in different responses; thus, one invasive species often affects multiple native animal species in different ways (Braithwaite et al 1989;Sogge et al 2008;Kapfer et al 2013;Mokotjomela et al 2013;Montiel-Mart ınez et al 2015;Rozen-Rechels et al 2017;Ranyard et al 2018). Comparative studies considering multiple animal species (Braithwaite et al 1989;Sogge et al 2008;Rozen-Rechels et al 2017;Ranyard et al 2018), multiple invasive plant species, or both (Trammell & Butler 1995) can provide insight into how native and invasive species' traits interact to shape the effects of invasive plants on behaviour, especially when traits are explicitly considered in predictions and analyses (Ceradini & Chalfoun 2017a;Rozen-Rechels et al 2017).…”
Section: Environmental Contextmentioning
confidence: 99%
“…First, context influences how modes of impact generated by an invader translate to behavioural changes. The characteristics of different animal species can result in different responses; thus, one invasive species often affects multiple native animal species in different ways (Braithwaite et al 1989;Sogge et al 2008;Kapfer et al 2013;Mokotjomela et al 2013;Montiel-Mart ınez et al 2015;Rozen-Rechels et al 2017;Ranyard et al 2018). Comparative studies considering multiple animal species (Braithwaite et al 1989;Sogge et al 2008;Rozen-Rechels et al 2017;Ranyard et al 2018), multiple invasive plant species, or both (Trammell & Butler 1995) can provide insight into how native and invasive species' traits interact to shape the effects of invasive plants on behaviour, especially when traits are explicitly considered in predictions and analyses (Ceradini & Chalfoun 2017a;Rozen-Rechels et al 2017).…”
Section: Environmental Contextmentioning
confidence: 99%
“…The effects of reed canary grass on wildlife species have been mixed, as demonstrated in results from experimental and correlational studies. Studies have found negative associations with swamp sparrow ( Melospiza georgiana ; Kirsch et al ), white‐footed mouse ( Peromyscus leucopus ; Spyreas et al ), Butler's garter snake ( Thamnophis butleri ; Kapfer et al ), and Oregon spotted frog ( Rana pretiosa ; Kapust et al ). Other work found no association between reed canary grass and common yellowthroat ( Geothlypis trichas ; Kirsch et al ), muskrat ( Ondatra zibethicus ; Cotner and Schooley ), American toad ( Anaxyrus americanus ; Maerz et al , Rittenhouse , Cohen et al a ), Oregon spotted frog (Popescu et al ), wood frog ( Lithobates sylvaticus ; Maerz et al , Rittenhouse , Cohen et al a ), pickerel frog ( L. palustris ; Cohen et al 2012 a,b ), Cope's gray treefrog ( Hyla chrysoscelis ; Rittenhouse ), and overall bird and mammal richness (Spyreas et al ).…”
mentioning
confidence: 99%
“…Other work found no association between reed canary grass and common yellowthroat ( Geothlypis trichas ; Kirsch et al ), muskrat ( Ondatra zibethicus ; Cotner and Schooley ), American toad ( Anaxyrus americanus ; Maerz et al , Rittenhouse , Cohen et al a ), Oregon spotted frog (Popescu et al ), wood frog ( Lithobates sylvaticus ; Maerz et al , Rittenhouse , Cohen et al a ), pickerel frog ( L. palustris ; Cohen et al 2012 a,b ), Cope's gray treefrog ( Hyla chrysoscelis ; Rittenhouse ), and overall bird and mammal richness (Spyreas et al ). Additionally, studies found positive associations between reed canary grass and sedge wren ( Cistothorus platensis ; Kirsch et al ), song sparrow ( Melospiza melodia ; Kirsch et al ), voles ( Microtus ochrogaster and Microtus pennsylvanicus ; Spyreas et al ), short‐tailed shrew ( Blarina brevicauda ; Spyreas et al ), and common garter snake ( Thamnophis sirtalis ; Kapfer et al ).…”
mentioning
confidence: 99%